SwabExpress: An End-to-End Protocol for Extraction-Free COVID-19 Testing. (7th October 2021) - Srivatsan, Sanjay; Heidl, Sarah; Pfau, Brian; Martin, Beth K; Han, Peter D; Zhong, Weizhi; van Raay, Katrina; McDermot, Evan; Opsahl, Jordan; Gamboa, Luis; Smith, Nahum; Truong, Melissa; et al.
Abstract: Background: The urgent need for massively scaled clinical testing for SARS-CoV-2, along with global shortages of critical reagents and supplies, has necessitated development of streamlined laboratory testing protocols. Conventional nucleic acid testing for SARS-CoV-2 involves collection of a clinical specimen with a nasopharyngeal swab in transport medium, nucleic acid extraction, and quantitative reverse-transcription PCR (RT–qPCR). As testing has scaled across the world, the global supply chain has buckled, rendering testing reagents and materials scarce. To address shortages, we developed SwabExpress, an end-to-end protocol developed to employ mass produced anterior nares swabs and bypass the requirement for transport media and nucleic acid extraction. Methods: We evaluated anterior nares swabs, transported dry and eluted in low-TE buffer as a direct-to-RT–qPCR alternative to extraction-dependent viral transport media. We validated our protocol of using heat treatment for viral inactivation and added a proteinase K digestion step to reduce amplification interference. We tested this protocol across archived and prospectively collected swab specimens to fine-tune test performance. Results: After optimization, SwabExpress has a low limit of detection at 2–4 molecules/µL, 100% sensitivity, and 99.4% specificity when compared side by side with a traditional RT–qPCR protocol employing extraction. On real-world specimens, SwabExpress outperforms an automated extraction system while simultaneously reducing cost and hands-on time. Conclusion: SwabExpress is a simplified workflow that facilitates scaled testing for COVID-19 without sacrificing test performance. It may serve as a template for the simplification of PCR-based clinical laboratory tests, particularly in times of critical shortages during pandemics.